Vulnerabilidad a infecciones de transmisión sexual y SIDA en mujeres en situación de desplazamiento forzado. Medellín, Colombia (2010)
ABSTRACT: To analyze the social vulnerability to sexually transmitted diseases and AIDS (STD, AIDS), in a group of women who arrived to the city of Medellin (Colombia) in forced displacement situation. Methodology: ethnographic qualitative study performed from April to August of 2008 in the city of Medellin. 23 women were interviewed in different health care providing institutions. Results: the abrupt change from their daily life, the social and family networks fragmentation, the gender status, and in some women the sexual violence before, during and after the displacement were related with a higher vulnerability to STD/HIV/AIDS in the studied population. Conclusion: the studied women vulnerability conditions belonging to this group of diseases began before the migration and were present during and after the displacement.